Study protocol for the randomized controlled trial of EMBOLDEN: a multifaceted intervention aimed at Enhancing physical and community MoBility in OLDEr adults with health inequities using commuNity co-design - Ganann, Rebecca; Phillips, Stuart M.; Neil-Sztramko, Sarah E.; Fisher, Kathryn; Alvarez, Elizabeth; Kuspinar, Ayse; Newbold, K. Bruce; Moore, Caroline; MacNeil, Maggie; Keller, Heather; Teggart, Kylie; Thabane, Lehana; et al. (Frontiers in Public Health, 2025)
BackgroundReduced physical mobility is common in older adults and is associated with adverse outcomes, including functional decline, depression, social isolation, and poor nutritional status. Group-based programs focusing on physical activity and nutrition to support healthier lifestyles have demonstrated benefits, particularly when paired with social engagement activities. This paper presents the protocol for a randomized controlled trial (RCT) to test a lifestyle intervention called EMBOLDEN: a multifaceted intervention aimed at Enhancing physical and community MoBility in OLDEr adults with health inequities using commuNity co-design. EMBOLDEN is a co-designed 3-month intervention to improve quality of life by incorporating physical activity, healthy eating, social participation, and system navigation. Participants receiving the EMBOLDEN intervention plus usual care are expected to show improvement in physical activity and other health outcomes compared to receiving usual care alone.MethodsThis is a 2-arm Type II hybrid effectiveness-implementation pragmatic RCT. Eligibility criteria include older adults (55+ years), community-dwelling in urban neighborhoods facing health inequities, able to speak or understand English or Mandarin (or access to family/friend interpreters), and able to walk 10 m unassisted by another person (assistive devices permitted). Participants will be randomized to the intervention or control arm (1:1 ratio). The intervention arm is usual care plus: (1) 12 weekly group-based sessions to increase knowledge/skills and behavior activation related to physical activity, healthy eating, fostering social connections and community resources; and (2) up to three tailored individual system navigation sessions. The control arm is usual care, in which participants identify and access services without research support. The primary outcome is time spent doing moderate-to-vigorous physical activity. Secondary outcomes will also be explored, including quality of life, life space mobility, depressive symptoms, nutritional risk, and loneliness. Data will be collected at baseline, 3 months (post-intervention) and 6 months. Mixed effects models will be used to analyze outcomes, intention-to-treat analysis will be employed, and multiple imputation will address missing data. Descriptive and qualitative data from participants, interventionists, and research documentation will be used to examine adaptations and implementation barriers/facilitators.DiscussionA community-based, co-designed lifestyle intervention may improve physical activity and other health outcomes in older adults living in neighborhoods with health inequities.Clinical trial registrationClinicalTrials.gov, NCT05008159.